2008
DOI: 10.1111/j.1365-2230.2007.02632.x
|View full text |Cite
|
Sign up to set email alerts
|

The controversial role of vitamin D in the skin: immunosuppression vs. photoprotection

Abstract: SummaryVitamin D is produced in the skin by ultraviolet (UV) B radiation (290-320 nm). The active metabolite 1,25-dihydroxyvitamin D 3 [1,25(OH) 2 D 3 ] is made systemically by hydroxylation of vitamin D in the liver and the kidney, but also locally in the epidermis, which suggests that 1,25(OH) 2 D 3 may have important functions in the skin. 1,25(OH) 2 D 3 has opposing effects: it can mimic immunosuppressive effects caused by UV irradiation in some models, or reverse UV-induced DNA damage and immunosuppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…113 As a steroid hormone, vitamin D exerts its effects by activating the nuclear vitamin D receptor. 125 Vitamin D's role in the photoaging process is still being uncovered with new information constantly emerging. In vitro, pretreatment with 1,25-(OH) 2 vit D 3 reduces UV-induced thymine dimers and apoptosis in keratinocytes.…”
Section: Vitamins As Therapymentioning
confidence: 99%
“…113 As a steroid hormone, vitamin D exerts its effects by activating the nuclear vitamin D receptor. 125 Vitamin D's role in the photoaging process is still being uncovered with new information constantly emerging. In vitro, pretreatment with 1,25-(OH) 2 vit D 3 reduces UV-induced thymine dimers and apoptosis in keratinocytes.…”
Section: Vitamins As Therapymentioning
confidence: 99%
“…In fact, 1,25-(OH) 2 D has been shown to be photoprotective and reduce UV induced DNA damage. [81] Studies aiming to investigate the effect of homeostatic 25-(OH) D levels and pharmacological supplementation on immune response to vaccination should also attempt to factor in UV exposure/season of study in addition to other variables discussed.…”
Section: Expert Commentarymentioning
confidence: 99%
“…110 The local immunosuppression induced by either UV irradiation or vitamin D continues, after the release of inflammatory cytokines, with their effect on epidermal LC. Vitamin D compounds were shown to have modulatory effects on dendritic cell maturation, differentiation, and activation in both human and murine culture systems, [115][116][117] probably via a VDR-dependent pathway [118][119][120] and furthermore to induce the inhibition of antigen presentation. 116,119 It has been suggested that the immunosuppression might be induced by the synthesis of active 1,25-(OH) 2 D 3 in the skin following UV irradiation.…”
Section: The Role Of Uv and Vitamin D On Skin Immunosuppressionmentioning
confidence: 99%